Taxation of Real Estate in Sweden (1862-2013) - Mikael Stenkula (Research Institute of Industrial Economics (IFN), 2014)
This paper examines the development and role of the real estate taxation in Sweden during the period between 1862 and 2010. Real estate has historically been taxed at both the local and state levels in Sweden. The importance of real estate taxation in Sweden is nevertheless difficult to assess directly because of the limited availability of data and the specific construction of the local tax system after 1920. The real estate tax initially aimed to provide municipalities with a stable tax base; however, its importance in this respect has diminished over time. After the tax reform of 1990-1991 in Sweden, real estate was taxed exclusively at the national level, generating tax revenue of approximately one percent of GDP. Further, in 2008, part of the tax was transformed to a local fee.
Keywords: H20; N43; N44; 330; Real estate tax; Property tax; Tax reforms